(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent years, increasing attention has been paid to liver diseases. One of the main reasons for this is the growing prevalence of these conditions worldwide every year, including in Uzbekistan, and the impact on the working-age population. Extensive prospective studies conducted in recent years in the United States have recorded new cases of chronic diffuse liver diseases at a rate of 63.9 per 100,000 people annually. Among these, two-thirds are diagnosed with hepatitis C virus (42%) or alcoholic liver disease (22%). Notably, in 20% of patients with chronic diffuse liver diseases, the first diagnosis of liver cirrhosis was made. All these facts highlight the importance of prevention, early detection, and treatment measures for liver diseases, which are not only medical but also of significant social importance.